The relative contribution of the raft in carrying Piled Raft foundation loads - مبارك, ثراء (Latakia University Journal -Engineering Sciences Series, 2024)
The Piled Raft system is a geotechnical composite foundation consisting of piles and raft (hat), with a high capacity against collapse. In traditional methods of the design of piles such as that adopted in the Syrian Arabic code, it is assumed that the role of the raft is to transport the load for piles, the total loads transferred from the building are distributed to piles only and therefore a large number of piles, while if the contribution of the raft is taken into account it can reduce the number of piles and thus reduce the economic cost. This research suggested a simplified method of calculating the contribution of the raft in carrying loads transferred from a previously studied building according to the Syrian Arab Code approach, this method relied on the principle of the additional impact of piles as raft pillars that reduce their settlement, this made the raft a judgment that contributed to the carrying of part of the loads, the raft's contribution rate to the suggested simplified method was 37.6% of the total load capacity, thus reducing the number of piles, meaning increasing the spacing between the pegs, this increases the efficiency of the work of the group of pegs in addition to reducing the economic cost. The suggested method was also compared with the Poulos method and the convergence between them reached 98.94%, the safety of the suggested method was also verified by calculating the safety factor according to Bandyopadhyay which reached FSPR = 4.28.